Assessment of foodborne disease hazards in beverages consumed in Nigeria: A systematic literature review - Oduori, David O.; Kwoba, Emmah; Thomas, Lian F.; Grace, Delia; Mutua, Florence K. (Mary Ann Liebert Inc, 2022)
Risk assessment is a formal process of identifying hazards and assessing the risk associated with them (risk is a combination of the severity of illness and the probability of occurrence). This review highlights foodborne disease hazards reported in beverages consumed in Nigeria for the period between 2000 and 2020. Based on a preregistered protocol and search syntax, studies were retrieved from the PubMed, Google Scholar, and ScienceDirect databases. Rayyan QCRI software was used to screen the articles. Data were then extracted from the included full-text articles, into a standardized excel workbook. A total of 18,762 articles were identified, from which 126 were included in the final analyses. The common beverages studied were sachet water (14.9%), borehole/well water (13.9%), cereal-based beverages (12.1%), raw/fresh milk (8.3%) and nono/nunu, which is a fermented milk-cereal beverage (7.2%). Sufficient data were available to undertake pooled prevalence estimates for some hazards within select beverages and revealed contamination rates for Staphylococcus spp. in raw/fresh milk, 12.3% (95% CI 6.3–20.0); Salmonella spp. in borehole/well water, 19.8% (95% CI 13.1–27.4); Klebsiella spp. in sachet water, 40.0% (95% CI 12.4–71.7); Staphylococcus spp. in nono/nunu, 32.6% (95% CI 14.7–53.8), and Escherichia spp. in nono/nunu, 30.7% (95% CI 21.9–40.2). Heterogeneity was present in the aggregate summary estimates. This review has highlighted the presence of several hazards of high importance to public health in commonly consumed beverages in Nigeria. The data presented here provide an entry point for future quantitative risk assessments both to determine the level of exposure of the community to these hazards and also for the identification of the most effective mitigation strategies to reduce these risks and improve health outcomes in Nigeria.